Families, values, and the transfer of knowledge in Northern societies, 1500-2000
1 online resource.
Keywords: "This edited collection sheds light on Nordic families' strategies and methods for transferring significant cultural heritage to the next generation over centuries. Contributors explore why certain values, attitudes, knowledge, and patterns were selected while others were left behind, and show how these decisions served and secured families' well-being and values. Covering a time span ranging from the early modern era to the end of the twentieth century, the book combines the innovative "history from below" approach with a broad variety of families and new kinds of source material to open up new perspectives on the history of education and upbringing"--